PARTISIPASI PEMILIH PADA PEMILIHAN UMUM DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI TAHUN 2010-2015 - Elwy Soehandry. S; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Election is a process by which voters choose people to fill certain political positions. Political positions vary from the President, representatives at various levels of government to the village head. The electoral system used in Indonesia is the principles of direct, public, free, confidential (overflow), as well as honest and fair. Election of the President, Legislative, and Regional Head directly for the purpose of choosing leaders directly and the people can determine the leaders they want more autonomy. The elections can not be separated from the participation of the community to participate in these elections. In Sub Tebing Tinggi voter participation rates in elections experiencing fluctuating numbers of voter participation in elections.This research was conducted in September and December 2016. The purpose of this study was to determine the cause of the rise and fall participation number of voters on Election in District Tebing Tinggi District maritime Meranti from 2010-2015. The method used in this research is descriptive qualitative method, which in this study researchers tried to explain the causes of voter turnout fluctuated in Tebing Tinggi District of Kepulauan Meranti Regency Year 2010-2015. Data collection techniques in this study using the technique of in-depth interviews and documentation relevant facts.From interviews to all informants and based on the data and information obtained by researchers when conducting research at the site, it can be concluded that the factors Cause Voter Participation in Tebing Tinggi District of Kepulauan Meranti Regency Year 2010-2015 seen from the following conditions are. First, Sociological conditions. This condition is associated sociological look at some aspects of the voters are divided into three parts, namely socio-economic factors, geographical factors, and ethnicity. Second, Psychological Condition. Instruments of this condition can be seen from the political beliefs of the candidates are divided into confidence and trust on the issue, as well as the political consciousness of the electorate is divided into autonomous participation and mobilization. Thirdly, options consisting Rational Choice Rational Fragmatis Idealists and options. Another factor that causes fluctuating voter participation is the difference the moment elections and election administrative and technical issues.Keywords: Election, Participation, Fluctuation